2021
DOI: 10.3389/fchem.2021.757826
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Drugs for SARS-CoV-2 Using Inverse Docking Fingerprints

Abstract: Severe acute respiratory syndrome coronavirus 2 or SARS-CoV-2 is a virus that belongs to the Coronaviridae family. This group of viruses commonly causes colds but possesses a tremendous pathogenic potential. In humans, an outbreak of SARS caused by the SARS-CoV virus was first reported in 2003, followed by 2012 when the Middle East respiratory syndrome coronavirus (MERS-CoV) led to an outbreak of Middle East respiratory syndrome (MERS). Moreover, COVID-19 represents a serious socioeconomic and global health pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 106 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…Several approaches were introduced to reveal potential antivirals against SARS-CoV-2. Among them, the first installed one was the usage of existing clinically approved drugs (i.e., re-purposing of drug usage) [ 15 ]. Nevertheless, undesired side effects may occur in terms of different doses, toxic effects, and pharmacological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches were introduced to reveal potential antivirals against SARS-CoV-2. Among them, the first installed one was the usage of existing clinically approved drugs (i.e., re-purposing of drug usage) [ 15 ]. Nevertheless, undesired side effects may occur in terms of different doses, toxic effects, and pharmacological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse molecular docking protocol based on the CANDOCK algorithm resulted in score variations for the detection of true target proteins (TG determined from PC has a value of 0.171), which in combination with ROC AUC above 0.6 indicates that the protocol provides good results in agreement with the experiments [ 61 ]. Moreover, our inverse molecular docking protocol has been already extensively validated by Fine and Konc et al [ 55 ], Furlan et al [ 50 , 130 ], Kores et al [ 49 , 131 ], and Jukič et al [ 132 ] using different molecules of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Enormous prevention efforts, including social distancing, regular use of masks and hand washing, have not prevented the spread of the virus [4]. Motivated by the rapid increase in cases and severe illness, much effort has been placed on the discovery of antivirals, by resorting to natural compounds or through drug repositioning strategies [5][6][7][8][9][10], along with vaccine development [11]. Although several commercialized drugs, such as Remdesivir [12] or Hydroxychloroquine [13], were initially repositioned as antivirals to treat severe COVID-19, subsequent large randomized clinical trials showed them to be ineffective or to exhibit unacceptable levels of side effects [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These features make M pro an attractive and obvious target to treat COVID-19. Designed druglike compounds such as noncovalent inhibitors [26], peptidomimetic inhibitors [23], drug repositioning and screening of natural compounds [5][6][7][8][9][10]21] are some examples of the strategies used to discover small molecules targeting SARS-CoV-2 M pro . In this regard, Virtual Screening represents an effective and reliable computational approach useful for the rapid identification of bioactive compounds directed against a target of interest [27,28], and thus many in silico studies have applied Virtual Screening protocols as the initial step towards the identification of potential M pro inhibitors [29][30][31][32][33], some of which have been experimentally confirmed [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%